Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„Ù‚Ø±Ø¢Ù† Ù„Ù„ÙØ±Ø§Ù‡ÙŠ ÙˆØ§Ù„Ù…ÙˆØ§Ø²Ù†Ø© Ø¨ÙŠÙ†Ù‡ ÙˆØ¨ÙŠÙ† Ø§Ù„Ø¨Ø±Ù‡Ø§Ù† ÙÙŠ Ø¹Ù„ÙˆÙ… Ø§Ù„Ù‚Ø±Ø¢Ù† Ù„Ù„Ø²Ø±ÙƒØ´ÙŠ - Abdullah , Mohd Farid Ravi; Usman, Abur Hamdi (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This study focused on the techniques of the Qurâ€™an, which is particularly selected due to the vital importance of making use of the linguistic techniques and employing them in studying the linguistic techniques of the Qurâ€™an which have convinced the majority of people to accept the principles of this religion, Islam, through their distinctive features which call attention to their research. Besides, there is a lack of studies which investigated and explained the formation and structures of the techniques of the Qurâ€™an, the techniques we are in dire need of to address others. It is noticed that the previous Qurâ€™anic studies have been more concerned with focusing many topics related to the sciences of the Qur'an but no study has examined the linguistic structures of the Qurâ€™an. Much research has studied the techniques of the Qurâ€™an; for instances some researchers investigated this topic independently such as al-FarahÄ«in his book AsÄlib al-QurÄn while others, like al-ZarkashÄ«, just discussed it in part of his book, al-BurhÄn FÄ«â€˜UlÅ«m al-QurÄn. Therefore, the present study investigates the approaches used by al-ZarkshahÄ«and al-FarahÄ«in studying the techniques of the Qurâ€™an in their books related to the sciences of the Qurâ€™an. To achieve the objectives of this study, the books related to the topic are collected and examined. Moreover, the approaches employed by al-ZarkashÄ«and al-FarahÄ«are analyzed and then the useful techniques which could be utilized for understanding the Qurâ€™an are also identified. The findings of the study reveal that al-FarahÄ«links the techniques of the Qurâ€™an with the coherence of the Qurâ€™an, which represents the objective unity of the whole Qurâ€™an. It is also shown that al-FarahÄ«believes that those who do not understand the techniques of the Qurâ€™an have missed the understanding of and thereflection on the Qurâ€™an. However, it is revealed that al-ZarkashÄ«makes the linguistic techniques independent from the objective unity of the Qurâ€™an.